2004
DOI: 10.2174/1381612043384655
|View full text |Cite
|
Sign up to set email alerts
|

The Antioxidants and Pro-Antioxidants Network: An Overview

Abstract: Living beings have evolved over the past two billion years through adaptation, to an increasing atmospheric oxygen concentration, by both taking advantage of oxygen activating function and developing a complex control network. In these regards, potentially damaging species (reactive oxygen, nitrogen and chlorine species) arise as by-products of metabolism and also work as physiological mediators and signalling molecules. Oxidative stress may be an important factor in numerous pathological conditions, i.e. infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
216
0
13

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 352 publications
(234 citation statements)
references
References 149 publications
5
216
0
13
Order By: Relevance
“…Secondly, it has been shown that ascorbate can recycle alpha-tocopherol, which in turn helps to prevent lipids oxidation. Without ascorbate, the alpha-tocopheroxyl radical can assume a prooxidant role and continue or even enchance the chain reaction of lipid peroxidation [20].…”
Section: A Ascorbic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, it has been shown that ascorbate can recycle alpha-tocopherol, which in turn helps to prevent lipids oxidation. Without ascorbate, the alpha-tocopheroxyl radical can assume a prooxidant role and continue or even enchance the chain reaction of lipid peroxidation [20].…”
Section: A Ascorbic Acidmentioning
confidence: 99%
“…For example, we have recently highlighted its possible role in the transport of drugs, which do not cross itself the blood brain barrier. In these regards, it may act as a double targeting molecule, working both as a carrier and as antioxidant in neurodegenerative diseases [20].…”
Section: A Ascorbic Acidmentioning
confidence: 99%
“…É importante lembrar que suplementos antioxidantes são sintéticos e possuem também propriedades pró-oxidantes (26) . Estes fatores poderiam explicar um possível aumento no risco de câncer (20,21,25) e doenças cardiovasculares (19) .…”
Section: Complicações Relacionadas Ao Uso Indiscriminado De Antioxidaunclassified
“…Por outro lado, depois de décadas de uso para prevenir e combater doenças sistêmicas, vários relatos demonstram que o uso indiscriminado de antioxidantes pode ser extremamente maléfico à saúde (19)(20)(21)(22)(23)(24)(25)(26)(27) .…”
Section: Introductionunclassified
“…Mentha pulegium (Lamiaceae) tea has been used as a traditional medicine for the treatment of fever, pain and dysentery (Vertuani et al 2004). Of note, M. pulegium was found to contain flavonoids that may account for the high antioxidant activity observed for the polar extracts of this aromatic herb (Zaidi et al 1998, Justesen andKnuthsen 2001).…”
Section: Introductionmentioning
confidence: 99%